Optimization of acid digestion methods for the determination of heavy metals in traditional medicine samples by atomic absorption spectrometry - Helal Uddin, A.B.M.; Khalid, Reem S.; Khan, Umeed Ali; Abbas, Syed Atif (2014)
Traditional/medicine (TM) has a significant contribution to the global health care system. During the past few decades the use of TM has progressively increased worldwide. Therefore, safety and quality of such products become a major concern. Some herbal medicines may contain toxic substances such as heavy metals. Arsenic (As), cadmium (Cd), lead (Pb) and nickel (Ni) are among the toxic heavy metals which may be present in some herbal products. Exposure to these metals can cause many adverse health effects, including cancer. Zinc (Zn) and iron (Fe) are essential metals to the human body at trace concentrations yet, they are toxic if present in higher concentration. Heavy metals content in TM products must accurately determine. Sample preparation is a critical step in spectroscopic analysis to achieve reliable and accurate results. Wet digestion methods are basically used for the dissolution of herbal products samples prior to elemental analysis. Therefore, this study has been designed to evaluate the efficiency of three acid digestion methods using different solvents individual and combination of classically used acids for wet digestion procedure to identify the optimal sample preparation method which was evaluated based on the highest analyte recovery. Five TM samples of herbal origin were selected to be digested with three different acid digestion methods namely A, B and C which represented a combination of nitric-perchloric acids HNO3 – HClO4, nitric acid HNO3 and a mixture of hydrochloric – nitric acids HNO3 – HCl respectively. The analysis of heavy metals was conducted using various techniques of atomic absorption spectrometer (AAS). Hydride generation (HGAAS) for As, graphite furnace (GFAAS) for Cd, Pb and Ni while flame (FAAS) was used for the analysis of Zn and Fe. The statistical analysis revealed that Method -C was the most efficient as it had given a significant high recovery (p<0.05) for of As, Cd, Pb, Ni, Zn, and Fe in all samples compared to Method -A and Method- B. Method- C was validated with analysis of Standard Reference Material 1515 (SRM) obtained from NIST and recovery percentage for As, Cd, Pb, Ni, Zn and Fe were 102, 96, 106, 94.5, 108 and 100 respectively.